The Use of Discourse Completion Task (DCT) As Explicit Instruction On Indonesian Efl Learners' Production of Suggestion Acts - Aufa, Fauzul (Journal of English and Education (JEE), 2011)
There are some activities that can be developed to bring up EFL learners' pragmatic awareness, such as contextualized language practice in given situations, constructed peer dialogues, and metapragmatic discussions. This task-based approach used in these activities can be either explicit or implicit instruction. One of them is a metapragmatic discussion prompted by Discourse Completion Task (DCT). In this paper, DCT, as an explicit pragmatic instruction, was practically investigated its effectiveness to facilitate EFL learners in developing their pragmatic competence. The results demonstrated from the analysis of RP2 prompted by the DCT support the fact that the explicit instruction results in some variations of linguistic forms that contribute to the development of subjects' pragmatic competence Key words : Discourse Completion Task (DCT), pragmatic competence, explicit pragmatic instruction, English as a Foreign Language (EFL).